Teaching Aids to Adults: A Resource for Acquired Immune Deficiency Syndrome Instruction - Appleby, George A.; Connecticut State Department of Education (State of Connecticut, Department of Education, 1989)
Keywords: AIDS (Disease); Study and teaching; dept.swk; faculty_collection

Review of Dependency and Poverty: Old Problems in a New World, by June Axinn and Mark J. Stern - Baskind, Frank R. (Journal of social work education, 1989)
0 citations (Crossref) [2023-10-31] tex.unique-id: ISI:A1989AN37000016
Keywords: dept.swk

Empowerment through collaboration in a state university system - Brower, Irene; Nancy Coleman; Ivry, Patricia; Leipzig, Barbara; Nemzer, Beatrice; Nilsson, Andrew; Sosnowitz, Barbara (Journal of Teaching in Social Work, 1989)
Historically, social workers have been aware of the power of group resources and the importance of networking for their clients and for themselves as professionals. This article is the outgrowth of a collaboration paper presented by the authors at the Association of Baccalaureate Social Work Program Directors Annual Conference on September 22, 1986 in San Antonio, Texas. Four separate social work education programs within a state university system formed an informal collaborative association to address common concerns, develop strategies to enhance resources and to foster mutual support. The context, developmental process, barriers, activities, issues, outcomes and benefits of the collaborative association are described. © 1989 Taylor & Francis Group, LLC.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/072-978-648-855-323 tex.type: [object Object]
Keywords: dept.swk

Social-work day to day - the experience of generalist social-work practice - wells,cc - Siegel, E (Journal of Social Work Education, 1989)
tex.unique-id: ISI:A1989AN37000014
Keywords: dept.swk; ⛔ No DOI found